(3GdEQTGO aj JaSjQ GdbQBfs - (3YHO GdSdGe Hf YHO GdQMef Hf eMeO GddNej GdETHjdj, CHh GdMce,J (B536 (3g` s
(3BNQgG (B:s
(3JfJgi HBNQ ShQI GdfUQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B18 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B69s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs